Advancing interdisciplinary research on illegal wildlife trade using a conservation criminology framework - Boratto, Rachel (European journal of criminology, 2021)
Green criminologists have recently entered a period of self-assessment, critiquing the discursive nature of theory, over-reliance on case studies, and lack of interdisciplinarity in this area of study, and offering a variety of ideas on how to move forward. We propose using conservation criminology, a multi/interdisciplinary and problem-specific research framework, to expand upon exploratory work through empirical research with clearly defined parameters. We use the illegal wildlife trade (IWT) as an example of the potential benefits of this approach, as this body of literature reflects the critiques raised by green criminologists. We further encourage the replication of important studies and the use of common terminology to describe study parameters to build towards greater generalizability that can be tested through meta-analyses and systematic reviews. This approach will help to build a body of interdisciplinary literature that can inform the development of empirically driven policy to address IWT and other environmental crimes and risks.